Financial Literacy for Early Childhood at Kindergarten - Asri Suwarsi, Aqidah; Noermawati, Julia; Utama, Satria; Robiatun, Fahmia; Anarika, Reza; Santosa Pambudi, Dwi (Publisher Cv. Inara, 2025)
Financial literacy is essential for children in early life in order to manage money effectively. In this study, the findings about early children financial literacy shifted from not literate to less literate after attending financial classes held by Universitas Muhammadiyah Yogyakarta (UMY). Meanwhile, parents of students report varying levels of literacy, ranging from less to sufficient literacy. This study employed an exploratory qualitative research approach. Researchers evaluated the comprehension and practices of preschool children and their parents in money management before and after receiving financial management training. The results are then analyzed and presented in the research report. The study was carried out in Aisyiyah Patosan Kindergarten, Sedayu, which is located in Magelang, Central Java, Indonesia.